The Effect of Small Sided Games Exercise and Vital Lung Capacity Toward VO2max in Football Players Age 14-17 - Triyanto, Triyanto; Rahayu, Setya; Wahyudi, Agung (Journal of Physical Education and Sports, 2021)
The players' aerobic endurance is insufficient, and as a result, they do not perform adequately during the competition. The purpose of this study was to analyze the effects of small-sided games with variations of 6vs6 (free touch) and 4vs4 (two touch), effects of high and low vital lung capacities, and interaction between Training methods and lung vital capacity on VO2max. Method used a quasi-experimental pretest-posttest design, 20 the sample 20 participants age 14-17 years old. Independent variables are Small-sided games and vital lung capacity, and dependent variables a VO2max. Multistage bleep test was employed as instrument for VO2max. Anova used to data analysis. Results that: 1) the 6vs6 variation (free touch) obtained a mean of 43.3, while the 4vs4 variation (two touch) obtained a mean of 40.2 with a value of (p=0.0030.05). 2) With a value of (p=0.000.05), high vital lung capacity obtained a mean of 44.6 and low vital lung capacity obtained a mean of 38.8. 3) small sided games activity with variants of 6vs6 resulted in a mean of 45.9 while a mean of 40.8 resulted in a low vital lung capacity. Small sided games exercise with variations of 4vs. resulted in a mean of 36.9 with a value (p=0.440>0.05). Conclusion that VO2max, practicing small-sided games 6vs6 version was better to practicing with the 4vs4 variation. VO2max member with high vital lung capacity was preferable to one with a low vital lung capacity. There was no interaction of training method and vital lung capacity toward VO2max.